MAKNA SEKOLAH BAGI ANAK USIA SEKOLAH DI KOTA SURAKARTA - Rohmad, Zaini; Chotidjah, Siti; Budiati, Atik Catur (Jurnal Inovasi Pendidikan, 2010)
This study aims to know the children's insight toward the existence of school as educational institution and to improve their critical awareness toward the real meaning of education. This study uses descriptive qualitative method for identifying the meaning of school, the impact of that meaning and the implications for the development of the educational system in Indonesia. The results show that school, for children, is defined as the process of knowledge transferring, hence it will be useful to seek jobs. This concept is also supported with schooling-oriented thinking. It means that children have to go to their school in order to meet their duty toward their parents and country. In boarder sense, school (or schooling) works as the representation of socio-cultural phenomenon because it contains such policies and programs issued politically in which the act of those is forced and dominated by the leaders. The effect of these situations is that the children lack awareness of the truly meaning of schooling. It implies that the school children are less good in daily life behaving and less in paying attention and caring of their surrounding environment. Based on those arguments, we need to train the children to act critically and improve their critical awareness so that the school children have good morality and attitude that make them useful for the existence of our nation.